PENGARUH KONSENTRASI CUKA KAYU DARI TEMPURUNG KELAPA TERHADAP KUALITAS IKAN GABUS (Ophiocephalus striatus) - Jelita, Rinny; Hadi, Abdul; Tuhuloula, Abubakar (Jurnal Riset Industri Hasil Hutan, 2012)
Vinegar wood is a mixture of solutions and dispersions of wood smoke from the pyrolysis. Pyrolysiswas doneat temperature of300oCfor 8hours and thesnake headfishpreservation processwas done bysoakingat vinegar woodconcentrationof 25%, 50% and 75% for 5minutes. Furthermorethe moisture of snake headfish was decreased before stored insealedjarsfor storage time during 1week, 2 weeksand 3weeks.The results showedthat therelative concentration ofphenol, aceticacid and carboxaldehydein coconut shellvinegar wood respectively by 21,65%; 47,90% and 4,54%. The moisture ofsnake headfish that storedfor 1weekwithvinegar woodconcentrationof 25%, 50%, and 75% respectively by60.7%, 66.67%, 67.8%and the moisture that storedfor 2and 3weeks respectively by67.5%, 69.76%, 72.09%, 72.41%, 73.91%, 72.22%. Protein of snake headfish that storedfor 1weekwithvinegar woodconcentrationof 25%, 50%, and 75% respectively by 10.93%, 70.8%, 9.95% and the protein that storedfor 2and 3weeksrespectively by7.07%, 7.05%, 6.99%, 4.55%, 6.49%, 6.79%. Number ofE.coli in snake head fish that storedfor 1weekwithvinegar woodconcentrationof 25%, 50%, and 75% respectivelyby 15APM/g, < 3APM/g, < 3APM/gand the number of E.coli that storedfor 2and 3weeksrespectively by240APM/g, 39 APM/g, < 3APM/g, >2400APM/g, 210 APM/g, < 3APM/g.Keywords: coconut shell, pyrolysis, vinegar wood, preservation, snake head fish